Nutrition literacy differs based on demographics among University students in Bengbu, China - Gao, Tianjing; Duan, Ying; Qi, Qi; Mo, Guangju; Han, Siyue; Liu, Huaqing; Zhang, Min (Frontiers in Public Health, 2023)
Background: Nutrition literacy (NL) encompasses the knowledge and skills that inform individuals’ food choices. This cross-sectional study explored factors associated with NL among Chinese university students in Bengbu, China. Methods: A cross-sectional survey was carried out. 2133 university students were selected by stratified cluster sampling. A 43-item NL questionnaire was used to assess NL. Binary logistic regression was used to determine odds ratios (ORs) along with 95% confidence intervals (CIs) for NL and to test the interaction effects of multiple factors on total NL and its six dimensions. Results:  Of these participants, 1399 (65.6%) were women and 734 (34.4%) were men. Students who were from urban areas (OR = 1.36, 95% CI: 1.08–1.72), were living with both parents (OR = 1.30, 95% CI: 1.02–1.65), and had high academic performance (OR = 1.85, 95% CI: 1.34–2.57) were more likely to report higher NL levels than did other students. The ORs for NL (OR = 1.60, 95% CI: 1.06–2.41), nutrition knowledge (OR = 1.51, 95% CI: 1.00–2.26), obtaining skills (OR = 1.76, 95% CI: 1.16–2.65), and critical skills (OR = 1.59, 95% CI: 1.05–2.39) were higher for medical students who had received nutrition education than for other students. The ORs for NL (OR = 2.42, 95% CI: 1.21–4.84), nutrition understanding (OR = 2.59, 95% CI: 1.28–5.25), and interactive skills (OR = 2.06, 95% CI: 1.04–4.08) were higher for only-child students and those with a monthly expenditure of >¥1500. Conclusions: NL of university students differed in terms of place of origin, living arrangement, nutrition education, academic performance, and household income, and the findings imply that universities should have all students take a basic nutrition course to improve their NL.